ANALISIS PENGARUH KUALITAS AUDIT TERHADAP EARNINGS MANAGEMENT - Haniatun Nihlati; Wahyu Meiranto (Diponegoro Journal of Accounting, 2014)
The purpose of this study was to examine the effect of audit quality and the relationship between earnings management. Indicators used to measure the characteristics of audit quality is a size of KAP, auditor industry specialization and auditor tenure. While the restatement of earnings as the dependent variable was measured by discretionary accruals and real earnings management. This study also added four control variables are firm size, growth opportunities, ROA, and leverage. The population in this study consist of all companies listed on the Indonesian Stock Exchange in year 2008 and 2012. Sampling method in this study is purposive sampling. The total number of final sample in this study were 199 entries. The analysis technique used is multiple regression. The empirical result of this study show that the auditor tenure has a negative relationship, while the firm size and auditor industry specialization has a positive relationship but all three did not have a significant effect on discretionary accruals. Furthermore, the size of the firm has a negative and significant effect on real earnings management, auditor industry specialization has a positive relationship and auditor tenure has no effect on real earnings management.